CALCULATION OF COEFFICIENTS CHANGES OF TERRIAN FOR AUTOMATION PLANNING WORK IN UPDATING DIGITAL TOPOGRAPHIC MAPS - Молочко, А.; Хірх-Ялан, В. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article considers the possibility of conducting determining the order sheet automation of digital maps on the degree of change in the area for planning and preparation work to update the digital maps based on GIS technologies. Keywords: geoinformation support, area analysis, information technologies